Production and separation of 163Ho for nuclear physics experiments. - S Heinitz; N Kivel; D Schumann; U Köster; M Balata; M Biasotti; V Ceriale; M De Gerone; M Faverzani; E Ferri; G Gallucci; F Gatti; et al. (PLoS ONE, 2018)
This paper describes the production and chemical separation of the 163Ho isotope that will be used in several nuclear physics experiments aiming at measuring the neutrino mass as well as the neutron cross section of the 163Ho isotope. For this purpose, several batches of enriched 162Er have been irradiated at the Institut Laue-Langevin high flux reactor to finally produce 6 mg or 100 MBq of the desired 163Ho isotope. A portion of the Er/Ho mixture is then subjected to a sophisticated chemical separation involving ion exchange chromatography to isolate the Ho product from the Er target material. Before irradiation, a thorough analysis of the impurity content was performed and its implication on the produced nuclide inventory will be discussed.